Pengaruh Pengembangan Sumber Daya Manusia Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Camat Siberut Selatan, Kabupaten Kepulauan Mentawai - Debi Alma Nofri Yantri; Khairil Aswan (Universitas 45 Surabaya, 2024)
This research aims to examine the influence of human resource development and work motivation on employee performance at the South Siberut District Head Office, Mentawai Islands Regency. This type of research is quantitative, the population in this research is all 35 employees. The sample collection technique used is a total sampling technique, where total sampling is a sampling technique if all members of the population are sampled, while the number of samples is 35 people obtained from all employee members. The type of data used in this research is quantitative data. Meanwhile, the data sources are primary and secondary data sources. Data collection techniques use observation and questionnaires. Using research instrument data analysis techniques (validity test, reliability test and descriptive analysis), classic assumption tests (normality test, multicollinearity test and heteroscedasticity test) then multiple linear regression analysis and hypothesis testing with the help of the SPSS application. The results of the research show that human resource development partially has a positive and significant effect on employee performance at the South Siberut Subdistrict Office, Mentawai Islands Regency.